Treatment of Fistula-In-Ano with Fistula Plug – a Review Under Special Consideration of the Technique - Köckerling, Ferdinand; Alam, Nasra N.; Narang, Sunil K.; Daniels, Ian R.; Smart, Neil J. (Frontiers in Surgery, 2015)
Introducation In a recent Cochrane review the authors concluded that there is an urgent need for well-powered, well-conducted randomized controlled trials comparing various modes of treatment of fistula-in-ano. Ten randomized controlled trials were available for analyses: There were no significant differences in recurrence rates or incontinuence rates in any of the studied comparisons. The following article reviews all studies available for treatment of fistula-in-ano with a fistula plug. Material and Methods PubMed, Medline, Embase and the Cochrane medical database were searched up to December 2014. 47 articles were relevant for this review. Results Healing rates of 50 – 60 % can be expected for treatment of complex anal fistula with a fistula plug, with a plug-extrusion rate of 10 – 20 %. Such results can be achieved not only with plugs made of porcine intestinal submucosa, but also those made of other biological mesh materials, such as acellular dermal matrix. Important technical steps in the performance of a complex anal fistula plug repair need to be followed. Summary Treatment of a complex fistula-in-ano with a fistula plug is an option with a success rate of 50 – 60 % with low complication rate. Further improvements in technique and better studies